Effectiveness of Play Approach in Improving Underhand Passing Skills in Volleyball Games in Children Aged 12-13 Years - Muhamad Hamdan Nurfazri; Akhmad Sobarna; Muchamad Ishak (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to analyze the effectiveness of the play approach in improving underhand passing skills in children aged 12-13 years. This study used a pre-experimental method with a Pretest-Posttest Control Group design. The sample consisted of 170 junior high school students in Saguling District, with 85 grade VII students of SMPN 1 Saguling as the experimental group and 85 grade VII students of SMPN 2 Saguling as the control group, selected through purposive sampling. The results showed that the play approach was significantly more effective than the conventional method. The average increase in scores in the experimental group was greater, with statistical tests showing a Sig. (2-tailed) = 0.000 (p <0.05). Cohen's d effect size test = 1.16 showed a very strong effect. The conclusion of this study shows that the play approach can be applied in physical education learning to improve basic volleyball skills and student motivation, and is recommended to be integrated into the school sports curriculum